Pelatihan Desain Media Pembelajaran Berorientasi Keterampilan Berpikir Kritis dan Kreatif Bagi Guru SD SN Najwa Rengas Pulau Kecamatan Medan Marelan - Yusmar Ali; Faudunasokhi Telaumbanua; Siti Aisyah (Journal of Social Responsibility Projects by Higher Education Forum, 2021)
Pandemic covid-19 impact not only the industrial sector but also the education sector .Partner devotion to the competitive it is a primary school teacher s najwa .Located at the primary school s najwa rengas marelan island in medan .This school has 60 10 teachers and students .For pandemics , policy learning in schools run face to face and turns , it was because the teachers do not have the capacity to media in designing creative learning for learning online .However , the quality of students continue to decline because of the short duration of study .Sehinggapermasalahan faced partner is human resources teachers who do not have the ability in terms of the use of technology and information especially design learning media , make the decreasing quality of student learning and interest The solution offered is giving training, teaching materials and design provide training to make video, ajar and provide training to make the evaluation of the learning process.A method to be implemented with the way of making speeches and practice of, with every 1 kind of training conducted 4x 2 hours meeting for 1 months. Through devotion for the public was teachers knowledge, the skill and partner and improve learning from these students discerned from learning outcomes.